Novel Antimalarial and Antitubercular Agents Based on Natural Products - Hans, Renate Hazel (Department of Chemistry, 2014)
Malaria and tuberculosis are listed among the major infectious diseases. They are responsible for severe morbidity and mortality especially in resource-poor settings where control interventions are inaccessible, unaffordable and plagued by widespread resistance. According to current estimates, malaria afflicts over 40% of the worldâs population and claims the lives of 1-3 million annually. The epidemiology of tuberculosis is just as grim. About one third of the world population is reported to be infected with Mycobacterium tuberculosis and it is responsible for 2-3 million deaths annually. Of particular interest to this project, is the fact that natural products have always been on the frontline in the battle against these diseases, that is, most of the clinically used drugs in antimalarial and antitubercular chemotherapy are of natural product-origin. In this project we therefore focussed on the design, synthesis, characterization and biological evaluation of novel antimalarial and antitubercular agents obtained by synthetically hybridizing and decorating scaffolds based on natural products or derivatives - with a history in the aforementioned disease models. Scaffolds selected include the thiolactone ring system, a key intermediate of the natural product thiolactomycin, the non-peptidic natural product isatin and the chalcone scaffold. In this way a series of hybrids were constructed which can be subdivided into three main groups: (i) thiolactone-isatin hybrids, (ii) -amino alcohol thiolactone-chalcone and isatin-chalcone hybrids, and (iii) dihydroartemisinin-isatin, dihydroartemisinin-chalcones and other miscellaneous hybrids. These were evaluated for antiplasmodial activity against the chloroquine resistant (W2) and chloroquine sensitive (D10) strains of Plasmodium falciparum as well as for inhibitory activity against cysteine proteases. Evaluation of antimycobacterial activity of the synthesized compounds against the drug sensitive H37Rv strain of M. tuberculosis was also undertaken. (i) For the first group of hybrids we used the C-4 hydroxyl group of the thiolactone ring as a handle for functionalization by attaching it via a variable, non-hydrolyzable alkyl linker to the isatin scaffold. Most striking, is the operational simplicity of the synthesis methodology employed and how it led to the discovery of a novel tetracyclic ring system. Identified from the latter is the compound 3.8p which is the most active antimalarial from this series with an IC50 of 6.92 Î¼M in the W2 strain. Some of the hybrids (3.7 and 3.8) were more active than the monomers and the parent drug thiolactomycin, thus demonstrating the potential of hybridization as a drug discovery tool. Antimalarial structure activity relationships for the novel tetracycles 3.8 revealed the importance of substitution at C-5 of the isatin scaffold and vi the need for increased lipophilicity. Although the antitubercular activity of the hybrids was inferior compared to the control drugs, a number of advanced intermediates were identified which displayed promising activity against both fast growing and slow-growing, persistent forms of M. tuberculosis. (ii) The second group of hybrids consisted of a 36-member library obtained by the covalent linkage of methoxylated chalcones with the thiolactone ring and the isatin scaffold. Incorporated in their design is the -amino alcohol moiety, a known bioactiphore. For the synthesis of these hybrids we employed the copper-catalyzed Huisgen 1,3-dipolar cycloaddition reaction (also know as âclickâ chemistry) which in addition to expediting structure activity relationship studies yielded the 1,2,3-triazole ring system. The antiplasmodial results showed that the thiolactone-chalcones, with IC50s ranging from 0.68 to 6.08 Î¼M, were more active against the W2 strain than the isatin-chalcones (IC50 = 2.09 - 14.90 Î¼M). More so, structure activity relationships delineated for the former indicated the preference for triOMe substitution on ring A of the chalcone scaffold. The most active compound for this series 4.14f [IC50 = 0.68 Î¼M (W2)] is 10-fold less active than chloroquine but has a greater efficacy than the parent natural product thiolactomycin. Results obtained for cysteine protease activity showed that the isatin-chalcone hybrids inhibited falcipain-2 activity, whereas the thiolactone-chalcone hybrids were devoid of enzyme inhibitory activity. With regard to antitubercular activity, the advanced intermediates were more active than the hybrid constructs. The most promising antitubercular agent identified is the acetylenic chalcone 4.10f (MIC = 13.1 Î¼M) which is 2-fold more active than one of the controls, moxifloxacin (MIC = 31.1 Î¼M) against the slow-growing persistent forms of M. tuberculosis. (iii) The final group of compounds is a limited series of semi-synthetic artemisinin analogues obtained by hybridizing the first generation analogue, dihydroartemisinin with previously mentioned scaffolds (isatin, chalcones, thiolactone) and other biologically relevant scaffolds such as the 4-aminoquinoline unit and azidovudine (AZT). As with the previous series we utilized the âclickâ reaction to effect the synthesis of these hybrids. The most active compound identified is the intermediate 5.4 [IC50 = 6.13 nM (W2)] which is more active than the parent natural product artemisinin [IC50 = 10.84 nM (W2)], 16 times more active than chloroquine and 2-times less active than dihydroartemisinin. The lack of antitubercular activity of compounds in this series moreover confirmed the antimalarial specificity of artemisinin analogues.